The Role of Ferroptosis in the Treatment and Drug Resistance of Hepatocellular Carcinoma - Zhao, Siqi; Zheng, Wubin; Yu, Chao; Xu, Gaoxin; Zhang, Xinyi; Pan, Chao; Feng, Yongheng; Yang, Kunxing; Zhou, Jin; Ma, Yong (Frontiers in Cell and Developmental Biology, 2022)
Cell death is a fundamental feature of multicellular organisms’ development and a key driver of degenerative diseases. Ferroptosis is a new regulatory cell death mediated by iron-dependent lipid peroxidation, which is different from apoptosis and necrosis in morphology, pathophysiology and mechanism. Recent studies have found that ferroptosis is involved in the development of many diseases including hepatocellular carcinoma (HCC). As further research progresses, specific mechanisms of ferroptosis in HCC are being revealed. In this review, we summarize these recent advances about the treatment of drug-resistance in HCC and the latest ferroptosis-related treatment for HCC.